2012
DOI: 10.1136/injuryprev-2012-040590q.15
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of screening for intimate partner violence, actual screening and satisfaction with care amongst female clients visiting a health facility in Kano, Nigeria

Abstract: BackgroundHealthcare providers have advocated for the screening and management of Intimate Partner Violence (IPV) against women and its consequences. Unfortunately, data from high income countries suggest that women may have varied preferences for being screened for IPV in healthcare. Although women's preference for screening in sub-Saharan countries has not been well researched, IPV remains an accepted societal norm in many of these countries, including Nigeria.ObjectiveThe objective of the study was to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…For example, while one study did not find a significant association between the time that IPA started and the length of marriage, [8] another study found the length of marriage to be a significant determinant. [19] In this study, only a slight difference was observed between the proportion that started IPA less than 2 years after marriage and those who did so two or more years after.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, while one study did not find a significant association between the time that IPA started and the length of marriage, [8] another study found the length of marriage to be a significant determinant. [19] In this study, only a slight difference was observed between the proportion that started IPA less than 2 years after marriage and those who did so two or more years after.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, introducing the routine screening of antenatal care attendees for IPA could help in early identification of women at risk of complications, thereby improving pregnancy outcome, an intervention which most of the women in a similar community were found to have accepted. [8] Finally, it is not clear why the prevalence of economic abuse was relatively low, despite the high proportion of the men admitting having abused their wife because of her poor economic status. Thus, future studies on IPA in such communities should include qualitative methods, to explore the contextual reasons that could explain such paradox.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Four parameters were chosen to measure the project's success because they were validated in previous studies and were determined to be the best for assessment in this study design 8 9. The outcomes were obtained via direct interviews with patient/client and staff using two different questionnaires.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…The acceptability of screening has also been found amongst women in a study conducted in Nigeria. 44 …”
Section: The Possibilities Of Domestic Violence Screening Treatment mentioning
confidence: 99%